Correlation of FDG‐PET hypometabolism and SEEG epileptogenicity mapping in patients with drug‐resistant focal epilepsy. (8th November 2016) - Lamarche, Florence; Job, Anne‐Sophie; Deman, Pierre; Bhattacharjee, Manik; Hoffmann, Dominique; Gallazzini‐Crépin, Céline; Bouvard, Sandrine; Minotti, Lorella; Kahane, Philippe; David, Olivier
Summary: Objective: Interictal [18F]fluorodeoxyglucose–positron emission tomography (FDG‐PET) is used in the presurgical evaluation of patients with drug‐resistant focal epilepsy. We aimed at clarifying its relationships with ictal high‐frequency oscillations (iHFOs) shown to be a relevant marker of the seizure‐onset zone. Methods: We studied the correlation between FDG‐PET and epileptogenicity maps in an unselected series of 37 successive patients having been explored with stereo‐electroencephalography (SEEG). Results: At the group level, we found a significant correlation between iHFOs and FDG‐PET interictal hypometabolism only in cases of temporal lobe epilepsy. This correlation was found with HFOs, and the same comparison between FDG‐PET and ictal SEEG power of lower frequencies during the same epochs did not show the same significance. Significance: This finding suggests that interictal FDG‐PET and ictal HFOs may share common underlying pathophysiologic mechanisms of ictogenesis in temporal lobe epilepsy, and combining both features may help to identify the seizure‐onset zone.